Dural Cavernous Sinus Fistulas Diagnostic and Endovascular Therapy - Benndorf, Goetz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Dural cavernous sinus fistulas (DCSFs) represent a benign vascular disease, consisting in an arteriovenous shunt at the cavernous sinus. In the absence of spontaneous resolution, the fistula may lead to eye redness, swelling, proptosis, chemosis, ophthalmoplegia and visual loss. Although modern imaging techniques have improved the diagnostic, patients with low-flow DCSFs are still misdiagnosed. These patients can get erroneously treated for infections and inflammation for months or years and are at risk of visual loss. Early and proper diagnosis helps to avoid deleterious clinical course of the disease. This volume provides a complete guide to clinical and radiological diagnosis as well as to therapeutic management of DCSF with emphasis on modern minimal invasive treatment options. It commences with an informative description of relevant anatomy. After sections on the classification, etiology and pathogenesis of DCSF, the clinical symptomatology of the disease is described in detail. The role of modern non-invasive imaging tools is then addressed with the use of computed tomography, magnetic resonance imaging and ultrasound. Intra-arterial digital subtraction angiography (DSA), although invasive, remains the gold standard and is mandatory for clinical decision-making and strategy in endovascular treatment. Hence, a throughout consideration is given to both, 2D-DSA and 3D rotational angiography, including recent technological advancements such as Dual Volume (DV) imaging and angiographic computed tomography (ACT). After a short section on arteriovenous hemodynamics, the therapeutic management of DCSFs is described in detail. In particular, various transvenous techniques, required for successful endovascular occlusion of DCSF, are discussed in depth. This well-illustrated volume will be invaluable to all who may encounter DCSF in their clinical practice.
Historical Considerations -- Anatomy of the Cavernous Sinus and Related Structures -- Classification of Cavernous Sinus Fistulas (CSFs) and Dural Arteriovenous Fistulas (DAVFs) -- Etiology, Prevalence and Natural History of Dural Cavernous Sinus Fistulas (DCSFs) -- Neuro-Ophthalmology in Dural Cavernous Sinus Fistulas (DCSFs) -- Radiological Diagnosis of DCSFs -- Endovascular Treatment -- Alternative Treatment Options -- Hemodynamic Aspects of DCSFs -- Summary.
Keywords: Medicine; Radiology, Medical; Interventional radiology; Neurology; Ophthalmology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Neuroradiology; Interventional Radiology; Neurology; Ophthalmology